Prior Anticoagulation and Short‐ or Long‐Term Clinical Outcomes in Ischemic Stroke or Transient Ischemic Attack Patients With Nonvalvular Atrial Fibrillation. Issue 3 (5th February 2019) - Tokunaga, Keisuke; Koga, Masatoshi; Itabashi, Ryo; Yamagami, Hiroshi; Todo, Kenichi; Yoshimura, Sohei; Kimura, Kazumi; Sato, Shoichiro; Terasaki, Tadashi; Inoue, Manabu; Shiokawa, Yoshiaki; Takagi, Masahito; et al.
Abstract : Background: We aimed to clarify associations between prior anticoagulation and short‐ or long‐term clinical outcomes in ischemic stroke or transient ischemic attack patients with nonvalvular atrial fibrillation. Methods and Results: A total of 1189 ischemic stroke or transient ischemic attack patients with nonvalvular atrial fibrillation who were hospitalized within 7 days after onset were analyzed. Of these, 813 patients (68.4%) received no prior anticoagulation, 310 (26.1%) received prior warfarin treatment with an international normalized ratio (INR) <2 on admission, 28 (2.4%) received prior warfarin treatment with an INR ≥2 on admission, and the remaining 38 (3.2%) received prior direct oral anticoagulant treatment. Prior warfarin treatment was associated with a lower risk of death or disability at 3 months compared with no prior anticoagulation (INR <2: adjusted odds ratio: 0.58; 95% CI, 0.42–0.81; P =0.001; INR ≥2: adjusted odds ratio: 0.40; 95% CI, 0.16–0.97; P =0.043) but was not associated with a lower risk of death or disability at 2 years. Prior warfarin treatment with an INR ≥2 on admission was associated with a higher risk of ischemic events within 2 years compared with no prior anticoagulation (adjusted hazard ratio: 2.94; 95% CI, 1.20–6.15; P =0.021). Conclusions: Prior warfarin treatment was associated with a lower risk of death or disability at 3 months but was not associated with a lower risk of death or disability at 2 years in ischemic stroke or transient ischemic attack patients with nonvalvular atrial fibrillation. Prior warfarin treatment with an INR ≥2 on admission was associated with a higher risk of ischemic events within 2 years. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT01581502.